THREE-DIMENSIONAL TOPOGRAPHIC MAPPING OF VERTICAL AND OVERHANGING SURFACES OF COASTAL CLIFFS USING UAV-BASED LIDAR DATASET A Case Study in South Kuta District, Bali Island: (Pemetaan Topografi Tiga Dimensi Permukaan Vertikal dan Menggantung dari Tebing Pantai Menggunakan Data LiDAR Berbasis Wahana Tanpa Awak: Studi Kasus di Kecamatan Kuta Selatan, Pulau Bali) - Daniel Adi Nugroho (Badan Informasi Geospasial, 2021)
The availability of high-density LiDAR datasets, enabled by UAV-based airborne laser scanning, has allowed topographic mapping surveyors to see unprecedented details on the earth’s surface. One of the problems faced in large-scale topographic mapping is generating proper three-dimensional contour lines for vertical cliffs, recesses, and overhangs, especially when the surface is covered by vegetation, which is quite common in the tropical area. This paper showcases the practical application of the LiDAR survey using an unmanned aerial vehicle and ground point classification process using the Simple Morphological Filter (SMRF) algorithm to produce high-fidelity, three-dimensional digital contour maps of coastal cliffs. By rotating the LiDAR dataset before the classification process to minimize overlapping surfaces, the entire dataset can be simulated as a 2.5-D surface. Therefore, the SMRF algorithm can be executed to classify all ground points on the cliff surface, including the overhangs and recesses. The resulting ground surface derived from this classification process provided a sufficient approximation of the real-world surface in overhanging cliffs and recesses while maintaining the conventional way to convey local landscape topography through three dimensional contour lines